Comparison of Different Simulation Tools for Load Flow Analysis in Power Systems - Nawaz, Sarfaraz; Bhardwaj, Ekta; Raj Sharma, Divyansh; Sharma, Divyanshu (International Journal of Advanced Engineering, Management and Science, 2023)
The comparative analysis provides valuable insights into the capabilities and limitations of different simulation tools, helping to improve the accuracy and efficiency of load flow studies, ultimately contributing to the reliable and secure operation of modern power systems. In this paper load flow analysis of IEEE 9 bus system is performed on three different software tools i.e. Power world simulator (PWS), MATLAB, MATPOWER. The results of load flow analysis of all three tools are compared. The economic load dispatch problem is also resolved in PWS and MATPOWER software. The results are promising and efficient when compared with latest ones.